2017
DOI: 10.30998/formatif.v6i3.990
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Kemampuan Berpikir Kritis dan Kemampuan Berpikir Kreatif

Abstract: <p><em>The purpose of the study was to determine the role of problem-based learning model to critical thinking ability and creative thinking ability. The subjects were students of semester IV Mathematics Education Study Program, University of Indraprasta PGRI, Jakarta in 2013/2014, in the subject of Basic Chemistry II. The selection of the class for this study was based on multistage random sampling. Experiments conducted on the sample of 30 experimental class students with problem-based learning m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
13

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 0 publications
0
12
0
13
Order By: Relevance
“…Pembelajaran berbasis masalah menjadikan perubahan dalam proses pembelajaran teacher centered menjadi student centered, sedangkan guru mengalami perubahan peran dari menjadi sumber pengetahuan menjadi fasilitator dalam memperoleh pengetahuan (Savery, 2015). Implementasi model problem based learning dapat melatih beberapa ketrampilan berpikir seperti berpikir kritis, menganalisis dan memecahkan masalah kompleks, kolaboratif, serta komunikatif secara verbal dan tertulis (Rosa & Pujiati, 2016 (Suhery, 2017). Melalui pembelajaran terintegrasi STEM siswa akan terbiasa memecahkan masalah, berpikir logis dan melek teknologi (Lou, et al, 2011 Hasil analsiis rata-rata N-gain kemampuan berpikir kritis pada kelas eksperimen adalah 0,56 dengan kategori sedang berdasarkan kriteria nilai N-gain (g) > 0,3 dengan kategori rendah, 0,3 ≥ g ≤ 0,7 dengan kategori sedang serta jika g > 0,7 berada pada kategori tinggi.…”
Section: Pendahuluanunclassified
“…Pembelajaran berbasis masalah menjadikan perubahan dalam proses pembelajaran teacher centered menjadi student centered, sedangkan guru mengalami perubahan peran dari menjadi sumber pengetahuan menjadi fasilitator dalam memperoleh pengetahuan (Savery, 2015). Implementasi model problem based learning dapat melatih beberapa ketrampilan berpikir seperti berpikir kritis, menganalisis dan memecahkan masalah kompleks, kolaboratif, serta komunikatif secara verbal dan tertulis (Rosa & Pujiati, 2016 (Suhery, 2017). Melalui pembelajaran terintegrasi STEM siswa akan terbiasa memecahkan masalah, berpikir logis dan melek teknologi (Lou, et al, 2011 Hasil analsiis rata-rata N-gain kemampuan berpikir kritis pada kelas eksperimen adalah 0,56 dengan kategori sedang berdasarkan kriteria nilai N-gain (g) > 0,3 dengan kategori rendah, 0,3 ≥ g ≤ 0,7 dengan kategori sedang serta jika g > 0,7 berada pada kategori tinggi.…”
Section: Pendahuluanunclassified
“…This means that PBL has procedures that allow students to enhance their skills and knowledge. In their research, Rosa and Pujiati (2016) suggested that the students taught using the PBL method possess a better critical and creative thinking ability. PBL help students cultivate their thinking competence and problem-solving skills so that they can become independent learners.…”
Section: Pbl On Students' Learning Outcomesmentioning
confidence: 99%
“…Susanti, 2013). While there is also research on PBL and its relation with biology and mathematics material and students 'thinking ability in university, that is about the influence of PBL on critical thinking and creative thinking skills of mathematics students (Rosa & Pujiati, 2016), PBL on students' metacognitive (Danial, 2010), PBL on the competence of biology students (Apriana & Anwar, 2014;Miharja, Syamsuri, & Saptasari, 2015). However, there is still a need for research on PBL in relation to the improvement of creative thinking skills, problem-solving skills, and learning outcomes in the context of CAR.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing student creativity is the impact of problem-based learning. Problem-based learning models influence students' creative thinking skills [16][17][18]. Increasing student creativity occurs because problem-based learning helps students to develop creative thinking skills [19,20].…”
Section: B Discussionmentioning
confidence: 99%